Do Different Types of Oil Price Shocks Affect the Indian Stock Returns Differently at Firm-level? A Panel Structural Vector Autoregression Approach - Aruna, Bhagavatula; Acharya, H. Rajesh (International Journal of Energy Economics and Policy, 2020)
In this paper, we investigate the dynamic relationship between different oil price shocks and Indian stock returns at firm level, using variable-structural VAR approach for the period 1995:01 to 2018:12. We use large unbalanced panel of 1768 manufacturing energy-intensive and non-manufacturing energy-intensive firms listed in the NSE. The estimation results depict that stock returns of India deteriorate due to disruptions in oil supply. In response to aggregate demand shock, stock returns and oil price move in opposite direction, whereas for speculative demand shock, oil price and stock returns have similar reactions. We also use GMM technique since our model suffers from endogeneity, thanks to the use of panel data. Since not all oil price shocks are alike, policy makers and investors should look into all aspects and sources of oil price shocks that impact stock returns, and make appropriate policy and investment decisions. From impulse response function, the effect is again cyclical as one could witness ups and downs in stock returns. This is because domestic oil price is partially dependent upon the status of subsidiaries and taxes. Also, inflation does not depend just upon oil price shocks and its sources, but it depends on other shocks such as inflation shock as well. Keywords: Oil price shocks; aggregate demand shock; speculative demand shock; structural vector autoregression; stock returns. JEL Classifications: C3, C5, G1, and Q4 DOI: https://doi.org/10.32479/ijeep.8891